2020
DOI: 10.1155/2020/1295984
|View full text |Cite
|
Sign up to set email alerts
|

Azelaic Acid Exerts Antileukemia Effects against Acute Myeloid Leukemia by Regulating the Prdxs/ROS Signaling Pathway

Abstract: Acute myeloid leukemia (AML) is a hematological malignancy with a poor prognosis attributed to elevated reactive oxygen species (ROS) levels. Thus, agents that inhibit ROS generation in AML should be exploited. Azelaic acid (AZA), a small molecular compound, can scavenge ROS and other free radicals, exerting antitumor effects on various tumor cells. Herein, this study evaluated the antileukemic activity of AZA against AML via regulation of the ROS signaling pathway. We found that AZA reduced intracellular ROS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Heat map analysis was used for separating fatty acids based on different concentration, represented from blue to green in decreasing order (Figure 5A). Fatty acids like stearic acid [55], linoleic acid [56], valeric acid [57], lauric acid [58] and azelaic acid [59] were already reported in the literature as strong antioxidants and stressreducing compounds. Principal component analysis (PCA) was used to understand the correlation among different groups, and we found that the fermented brown rice sample (Ferm L. reuterii AKT1) was divergent from the other three samples.…”
Section: Fatty Acid Composition In Brown Rice Samplesmentioning
confidence: 99%
“…Heat map analysis was used for separating fatty acids based on different concentration, represented from blue to green in decreasing order (Figure 5A). Fatty acids like stearic acid [55], linoleic acid [56], valeric acid [57], lauric acid [58] and azelaic acid [59] were already reported in the literature as strong antioxidants and stressreducing compounds. Principal component analysis (PCA) was used to understand the correlation among different groups, and we found that the fermented brown rice sample (Ferm L. reuterii AKT1) was divergent from the other three samples.…”
Section: Fatty Acid Composition In Brown Rice Samplesmentioning
confidence: 99%
“…In our previous reports on drug screening using a PDX model of HLL, B-NSG mice in the 2.5 Gy group survived beyond 20 days when injected with other HLL cells without malignant gene mutations [28], and B-NSG mice without irradiation survived beyond 31 days when injected with human AML cells separated from a hyperleukocytic AML-M5 patient with NPM1 and DNMT3A mutations [29]. In addition, the B-NSG mice with 1.5 Gy irradiation survived beyond 20 days when injected with human AML cells separated from a hyperleukocytic AML-M5 patient with WT1, DNMT3A and FLT3 mutations [30,31]. The mutational status of AML cells is also a key factor in immunode cient mice for the construction of a PDX model [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous reports on drug screening using a PDX model of HLL, B-NSG mice in the 2.5 Gy group survived beyond 20 days when injected with other HLL cells without malignant gene mutations [29], and B-NSG mice without irradiation survived beyond 31 days when injected with human AML cells separated from a hyperleukocytic AML-M5 patient with NPM1 and DNMT3A mutations [30]. In addition, the B-NSG mice with 1.5 Gy irradiation survived beyond 20 days when injected with human AML cells separated from a hyperleukocytic AML-M5 patient with WT1, DNMT3A and FLT3 mutations [31,32]. The mutational status of AML cells is also a key factor in immunode cient mice for the construction of a PDX model [33,34].…”
Section: Discussionmentioning
confidence: 99%